PENGEMBANGAN MEDIA PEMBELAJARAN MENYIMAK DONGENG BERBASIS STRATEGI METAKOGNITIF SISWA SMPN 1 TARUSAN KELAS VII - Yulia Novita; Anggun Cantika; Afnita Afnita (CARAKA, 2019)
Metacognitive strategies are the needs of today's students, for example, information processing processes. This is inseparable from the design of the steps of listening, listening, and post-listening learning. An essay test is used to analyze, evaluate, and create. In general, this study aims to develop learning media to listen to fairy tales based on Metacognitive strategies. Therefore, the research model of the development of Borg and Gall was used. Product trials involving learning media experts produced a product average of 75%, experts listened to 87%, 90% expert practitioners, and 91% field test students. Based on the test results from instructional media experts, learning media products are classified as feasible and ready to be implemented, but there are several aspects that need to be revised.